The Screen as a Shield: Internet Addiction as a Maladaptive Defense Against Childhood Emotional Neglect in a Left-Behind Adult - Made Citra Riesti Wulan; Wayan Wiradana (Scientia Psychiatrica, 2025)
Introduction: Internet addiction (IA) is frequently conceptualized as an impulse control disorder driven by dopaminergic dysregulation. However, in the context of left-behind children—those raised by grandparents due to parental migration—IA may function as a complex psychodynamic defense mechanism. This study aims to elucidate the role of the smartphone as a digital shield against the resurfacing trauma of Childhood Emotional Neglect (CEN) and attachment deficits. Case presentation: We report the case of a 23-year-old female in Eastern Bali presenting with acute dysphoria, elective mutism, and total insomnia following the confiscation of her smartphone. Assessment included the Internet Addiction Test (IAT), clinical interviews utilizing written communication during the mute phase, and family system analysis. The patient scored 58 on the baseline IAT, indicating moderate addiction. Clinical inquiry revealed a history of split-parenting, where the patient was reared by emotionally distant grandparents. The smartphone served a specific function of displacement, seeking safety in online relationships, and dissociation, used to numb loneliness. The device confiscation triggered a traumatic re-enactment of early childhood abandonment, resulting in physiological hyperarousal incompatible with the moderate IAT score. Treatment involved Fluoxetine (20mg), Clobazam (10mg), and psychodynamic psychotherapy focusing on attachment repair. At the 4-week follow-up, the IAT score decreased to 32, and verbal communication was fully restored. Conclusion: IA in young adults with developmental trauma functions as a maladaptive defense mechanism (The Digital Shield). Clinicians must address the underlying attachment wound rather than focusing solely on digital detoxification to achieve sustainable remission.